Evaluasi Penurunan Kecelakaan Kerja di Kapal Melalui Penerapan Aturan Emas HSSE Secara Efektif - Inaya Ajeng Larasati; Romanda Annas Amrullah; Vigih Hery Kristanto; Bugi Nugraha (Universitas Muhammadiyah Manado, 2025)
In the shipping industry, safety on board is one of the serious challenges that must be addressed due to the high risk of occupational accidents. PT X implements the HSSE Golden Rules, which consist of the principles of compliance, intervention, and care as a preventive measure to reduce the level of work accident.. This study aims to analyze the implementation of HSSE Golden Rules in reducing the level of work accidents on board PT X. The research method used is descriptive qualitative with data collection techniques in the form of interviews (through online forms) and documentation of unsafe action, unsafe condition, and nearmiss reports. The data analysis technique used is Strengths, Weakness, Opportunities, Threats (SWOT) analysis. The result show that the HSSE Golden Rules are eable to reduce the level of work accidents on ships, as evidenced by the decrease in the number of unsafe action, unsafe condition, and nearmiss reports from 2023 to 2024. More structured reports that include corrective actions indicate the formation of a better reporting and prevention culture. It can be concluded that the implementation of HSSE Golden Rules is effective in forming a safety culture and can reduce the level of work accidents on PT X ships.